Construction of identities of fruitful seasonal women in Chile: The case of Palqui: 1969-1997 - Arteaga Aguirre, Catalina (1998)
In the last decade, the approaches that have been used from the Social Sciences to address the study of rural reality have been turning from traditional perspectives - fundamentally represented by structuralist approaches, which prioritized the study of economic aspects - to other most innovative, which emphasize the subjects that interact in rural areas and seek, rather than impose certain models, to unravel the meanings and meanings that are part of the increasingly complex reality, giving voice to the inhabitants of these areas with the object of analyzing the impact that the agrarian transformations have implied for the daily life and the subjectivity of the rural population.